2015
DOI: 10.1007/s11145-015-9546-3
|View full text |Cite
|
Sign up to set email alerts
|

(Dis)connections between specific language impairment and dyslexia in Chinese

Abstract: Specific language impairment (SLI) and dyslexia are found to co-occur in school-aged children learning Chinese, a non-alphabetic language (Wong, Kidd, Ho, & Au, 2010). This paper examined the 'Distinct' hypothesis-that SLI and dyslexia have different cognitive deficits and behavioural manifestations (e.g., Catts, Adolf, Hogan, & Weismer, 2005)-which has been proposed to explain the relationship between SLI and dyslexia, in Chinese children in Primary 1. Ninety-four six-to seven-year-old Chinese children comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Another study compared some cognitive skills of Chinese first graders with DD, specific language impairments (SLI), and DD + SLI [34]. They reported that orthographic skills and rapid naming were associated with dyslexia; phonological memory and morphological awareness were associated with SLI; and phonological awareness was associated with both.…”
Section: Cognitive Profiles Of Reading and Spelling Difficulties In Cmentioning
confidence: 99%
“…Another study compared some cognitive skills of Chinese first graders with DD, specific language impairments (SLI), and DD + SLI [34]. They reported that orthographic skills and rapid naming were associated with dyslexia; phonological memory and morphological awareness were associated with SLI; and phonological awareness was associated with both.…”
Section: Cognitive Profiles Of Reading and Spelling Difficulties In Cmentioning
confidence: 99%
“…Importantly, speed of processing is also slower in children with specific language impairment (Leonard et al, 2007;Miller, Kail, Leonard, & Tomblin, 2001). Despite the ongoing debate on whether developmental dyslexia and specific language impairment should be regarded as two distinct disorders or different manifestations of the same underlying deficiencies, significant overlap between the two had been found, indicating their comorbidity (Catts, Adlof, Hogan, & Weismer, 2005;Wong, Kidd, Ho, & Au, 2010;Wong et al, 2015). Deficits in processing speed may turn out to be a shared cognitive risk factor that can help explain the comorbidity of these two disorders.…”
Section: Clinical and Educational Implicationsmentioning
confidence: 99%